Soybean‐oil‐based thermosetting resins with methacrylated vanillyl alcohol as bio‐based, low‐viscosity comonomer - Zhang, Yuehong; Thakur, Vijay Kumar; Li, Yuzhan; Garrison, Thomas F.; Gao, Zhenhua; Kessler, Michael R. (Wiley, 2017)
A novel, bio-based, aromatic monomer (methacrylated vanillyl alcohol, MVA), was synthesized using vanillyl alcohol and methacrylic anhydride in the absence of solvents. The resulting MVA was characterized and used as a sustainable reactive diluent to replace styrene in a maleinated acrylated epoxidized soybean oil (MAESO) resin to produce novel thermosetting resins via free radical polymerization. The influence of MVA loading (10 - 40%) on the viscosity, gelation time, curing extent, thermo-mechanical properties, and tensile properties of the MAESO-MVA copolymer was investigated. The synthesized MVA exhibited very low volatility relative to styrene, which is beneficial for the development of construction material with low or zero emission. With 40 wt% of MVA content in MAESO, a significant reduction of system viscosity (over an order of magnitude) was achieved. Increasing the MVA content accelerated the crosslinking reaction rate and improved thermal and mechanical properties of the MAESO-MVA system. The glass transition temperature increased with increasing MVA content. Soxhlet extraction experiments showed that more than 90% of the components were incorporated into the crosslinking network. The effect of MVA purity on the properties of the resulting copolymer was also investigated. MAESO-MVA copolymers prepared using high-purity MVA exhibited higher degree of crosslinking.
Keywords: Vanillin; Methacrylated vanillyl alcohol (MVA); Reactive diluent; Maleinated acrylated epoxidized soybean oil (MAESO); Thermosetting resin; Sustainable; Styrene replacement